Adaptive modeling and parameter identification of piezoelectric structures under system uncertainty and nonlinear effects - Maruccio, Claudio; Montegiglio, Pasquale; Kendibilir, Abdullah; Kefal, Adnan (Mechanical systems and signal processing, 2025)
A novel robust synchronization-based computational strategy is developed capable of identifying material and system parameters of active flexible smart structures and modeling the nonlinear response due to faults and system reconfiguration even in the presence of noise in the experimental data and uncertainties. The sensitivity problem, resulting from the gradient-based algorithm, is addressed with a novel hybrid technique that exploits the advantages of both frequency and time-domain procedures. This hybrid approach ensures robust parameter identification and accurate modeling under challenging conditions making it highly suitable for real-time applications. Extensive numerical results confirm the intrinsic benefits of the proposed computational strategy, demonstrating its effectiveness for simulating the response of nonlinear electromechanical vibration-based devices. The proposed approach is validated through its application to parameter identification and damage diagnosis of a sandwich laminate, showcasing its practical relevance and versatility. These advancements represent a significant step forward in the modeling and control of piezoelectric smart structures, offering a robust solution for applications ranging from structural health monitoring to energy harvesting.